Construction of Alternative Axial Points Using Standard Axial Points of Central Composite Design - Ugbe, Thomas; Edet Bassey; Richmond Ofonodo; Uduakobong Umondak (American Scientific Research Journal for Engineering, Technology, and Sciences, 2022)
There has been an over-flogged attention given to propositions on how one can make good choice of the existing axial points rather than procedural techniques for constructing axial points about the existing axial points. In order to curb this oversight, this work has constructed axial points about the standard axial points. The construction has given rise to * = 0.99k (where k is the number of factors) in comparison to the standard axial points = (where f is the number of factorial points). Both axial points have been implemented on a central composite design used for maximizing a four-factor process. The constructed axial points produced yields of about 87.211%, better than the yield of 87.187% produced by the standard axial points. Furthermore, the central composite design resulting from the constructed axial points satisfied the D-, A- and E-optimality criteria in comparison to that obtained from the standard or existing axial points.